Loss of Meanings of Cultural Metaphors: An Analysis of Taufiq Rafat’s Translation of Bulleh Shah’s Punjabi Poetry - Sanna Asghar (University of Chitral Journal of Linguistics and Literature, 2021)
Language encompasses the whole native culture and social norms and traditions but the translation from one language to another changes the context and sometimes meanings as well. The translators feel difficulties in finding word equivalences. Sometimes the equivalence of the words of one culture does not exist in the other culture which creates difficulties in translation to convey the complete message. There are so many issues while translating the Punjabi language into English. There are so many metaphors in Punjabi which do not have words equivalence in the English language. The research project aimed to trace out the loss of the meanings and context while translating Punjabi poetry into English. Many Punjabi Sufi writers have projected the colors of Punjabi in different forms and contexts but Bulleh Shah has a very unique style. Two poems of Bulleh Shah translated by Taufiq Rafat were under examination. This was a purely qualitative research where data has been collected from books, libraries, and research journals. Textual analysis has been used as a research method to analyze the data. The findings revealed that Punjabi poetry has distinct metaphors that represent Punjabi culture, but when translated into English the original meaning is lost.